Pengaruh Kecanduan Merokok dan Vape pada Remaja: Literatur Review - Telsa Amanda; Tursina Tursina; Marniati Marniati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The habit of smoking and using e-cigarettes (vape) among adolescents in Indonesia shows a significant increasing trend. This study aims to conduct a systematic review of various factors that influence dependence on cigarettes and vapes in adolescents, by analyzing 30 national scientific articles. The results of the review revealed that the dominant factors contributing to this behavior include the influence of the friendship environment, permissive parental attitudes, lack of knowledge, psychological pressure, and exposure to the media. In addition, education was found to be an effective strategy in increasing understanding and reducing smoking intentions. This behavior is also driven by the mistaken view that vaping is considered safer than regular cigarettes. This study suggests the need for a cross-sectoral approach, which includes ongoing education, regulatory enforcement, and the active role of families and educational institutions in efforts to prevent and control cigarette and vape addiction among adolescents.